Automatically grading essays with markit? - Williams, Robert; Dreher, Heinz (The Informing Science Institute, 2004)
Markit is an Automated Essay Grading (AEG) system capable of running on typical desktop PC platforms. Its performance compares favourably with human graders and with commercially available systems.A distinct advantage of Markit over existing commercial systems is that it requires only one model answer against which the student essays are compared. In this paper we report on a trial of Markit with second year law students? essays.